Peluang dan Hambatan Digital dalam Pembelajaran Bahasa Arab : Prespektif Guru dan Mahasiswa - Abdurahman Abdurahman; Arum Tri Budiarti; Khairun Nisa; Sahkholid Nasution (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The development of digital technology has a major impact on Arabic language learning, both in terms of opportunities and obstacles. This journal aims to identify opportunities and obstacles in Arabic language learning from the perspective of teachers and students. This research approach uses qualitative methods with interviews and literature studies to obtain a comprehensive picture of how digital technology can improve or hinder the Arabic language learning process. The results of the study indicate that the existence of digital technology provides many great opportunities for Arabic language learning, including: First, access to learning materials becomes wider. Second, there is global interaction. Third. Learning becomes more innovative and interesting. Fourth. Efficiency of time and place of learning. Fifth. The existence of digital technology can help advance educational institutions to the international level. However, there are also significant challenges from the existence of digital technology in Arabic language learning, including: First, the lack of maturity of teachers and students in using and utilizing digital technology. Second, there is digital distraction. Third, there is a technological gap and others.